A study of the health implications of mobile phone use in 8-14s (2017)
Mobile phone use is increasing worldwide. The physical, cognitive and social health implications of mobile phone use in young users are considered. A survey of 168 children aged 8-11 and 136 children aged 11-14 is reported. Participants completed questionnaires about their mobile phone use with follow-up interviews to elicit more in depth information about reasons for using mobile phones. Findings suggest users are at risk of muscular skeletal problems from mobile phone use, radio frequency damage from storage of the phone on the body, particularly when the person is ‘on the move’, and impaired performance from multi-tasking and sleep disturbance. Since long term or heavy usage of mobile phones is an unknown factor, caution is needed with regard to the risks associated with these findings.